KARAKTERISTIK KASUS FRAKTUR EKSTREMITAS BAWAH DI RUMAH SAKIT UMUM DAERAH DR H CHASAN BOESOIRIE TERNATE TAHUN 2018 - Utari Nurul Ridwan; abdul Muthalib Pattiiha; prita aulia selomo (Kieraha Medical Journal, 2020)
Background: Lower extremity fracture incident has a high prevalence in accident which approximately numbered in 40%. Fracture is a bone discontinuity or the broken off of bone structure unity which could be a fracture, crumbling, or a part of cortex got broken. The prupose of this research is to figure out the charactertistic of lower extremity fracture case in Dr. H. Chasan Boesoirie Ternate Regional General Hospital in the year 2018. Method: This research is a descriptive research, which take place in Dr. H. Chasan Boesoirie Ternate Regional General Hospital at the 30th of December 2019 until 6th of January 2020. The gathering of sample is conducted with total population sampling from secondary data,which is medical records that has fulfill the inclusion criteria, 51 sample has been gathered. The variabel that is observed is the patients profil which covers: age, sex, the cause of fracture, the location of fracture, kind of fracture, and type of fracture. The process of data analyzing is processed through the SPSS program. Results: The result of this research finds that the most common case of lower extremity fracture occure at the age > 18 years old (66%). The case is mostly occur in male patient (76%). Traffic accident (66%) became the main cause of lower extremity fracture. Closed fracture cases (74%) is commonly found in femur fracture (44,7%) with a complete fracture type (89,4%). Conclusion: The most common case of lower extremity fracture happen to a male at a productive age due to a traffic accident. The most common type of fracture is a femur fracture with a complete fracture type. Keywords : age, fracture, kind of fracture, lower extremity, sex.